"Where we wanna be": The role of structural violence and place-based trauma for street life-oriented Black men navigating recovery and reentry. (November 2018) - Yu, Anta F.; Hope House Men and Alumni,
Abstract: In this study, we used photovoice and grounded theory to understand the barriers and resources encountered by Black men navigating substance use recovery and/or reentry following incarceration in an urban, economically disadvantaged neighborhood. The conceptual framework that emerged highlighted the significant impact of traumatic disruptions to place and relationships, as well as an ongoing dialectical tension between considering passive participation in street life or choosing recovery. Regarding action steps, participants recommended investing in community infrastructure, rehabilitating adults to be mentors, and mentoring youth to prevent street involvement. Results highlight the importance of using trauma-informed interventions and participatory methods to improve health at individual and community levels. Highlights: Photovoice and grounded theory were used to understand the process of recovery/reentry for street life-oriented Black men. Results highlight the significant impact of structural violence and traumatic disruptions to place and relationships. Participants recommended investing in community infrastructure, rehabilitating adults, and mentoring youth. Our study supports the need for trauma-informed interventions and participatory methods to improve community health.